Proteomes of aging and omega-3 supplementation in rat soleus skeletal muscle. - Francesco Maria Del Re; David W Russ; Kalina P Dimova; Stylianos P Scordilis (PLoS ONE)
Aging is a pan-organ process with an intricate and multimodal nature. Deciphering the aging phenomenon is complex, yet recent attention is analyzing the potential benefits of non-invasive life adjustments to achieve healthy aging. Omega-3 polyunsaturated fatty acids (FA) have emerged as promising nutraceuticals for a plethora of different medical conditions. In the current study we conducted an in-depth, bottom-up, global, shotgun proteomic study (LC-MS/MS) investigating both the effects of aging on skeletal muscle and the potential alterations due to ω-3 FA. Sprague Dawley rats were fed different diets and divided into four groups (n = 5 per group): adult controls (7-8 months, ADCTL); aged controls (22 months, AGCTL); and adult (ADω3) and aged (AGω3) rats fed an ω-3 supplemented diet. Among the identified 30,000 soleus proteins, our proteomic analysis identified 149 proteins differentially expressed in aging; 207 proteins with aging, but fed ω-3 FA; and 105 and 26 proteins, respectively, when aged and adult rats were fed ω-3 FA. Aging alone (ADCTL/AGCTL) affects many processes: carbohydrate and lipid metabolisms, proteostasis, mRNA processing and sarcomeric proteins. With FA supplementation and aging (ADω3/AGω3) similar processes were affected, but increased chromatin-related protein abundances (methylation or histone deacetylation) were observed in AGω3; while proteins involved in OXPHOS and mitochondrial homeostasis, including mTOR, were more represented in ADω3 rats. Supplementation with FA had a greater effect in aged rats (AGCTL/AGω3) than in adult ones (ADCTL/ADω3). In the ADCTL/ADω3 comparison, modest changes were seen, whereas in the AGCTL/AGω3 comparisons DNA damage repair increased and protein synthesis and degradation were observed. Further, a potential link to enhancement of myogenesis is also evident. The data presented in this work suggest potential beneficial and protective effects of ω3 FA supplementation in the soleus muscle, as well as some potential molecular mechanisms of action.